Application of Langmuir and Dubinin–Radushkevich models to estimate methane sorption capacity on two shale samples from the Upper Triassic Chang 7 Member in the southeastern Ordos Basin, China. Issue 1 (January 2017) - Chen, Lei; Jiang, Zhenxue; Liu, Keyu; Ji, Wenming; Wang, Pengfei; Gao, Fenglin; Hu, Tao
A series of methane sorption isotherms were measured at 303 K, 313 K, 323 K, 333 K, and 343 K at pressures up to 12.0 MPa for two shale samples from the Upper Triassic Chang 7 Member in the southeastern Ordos Basin with total organic carbon content values of 5.15% and 4.76%, respectively. Both the Langmuir- and Dubinin–Radushkevich-based excess sorption models were found to well represent the excess sorption isotherms within the experimental pressure range. The maxima of absolute methane sorption capacity fitted by both models are not significantly different. In the current study, the effects of temperature and pressure on methane sorption capacity support the findings that under isothermal condition, methane sorption capacity of organic shale goes up with increasing pressure and under isobaric condition, while it goes down with increasing temperature. Good negative linear relationships between temperature and maximum sorption capacity exist both in the Langmuir and the Dubinin–Radushkevich models. In addition, a good positive linear relation exists between the reciprocal of temperature and the natural logarithm of Langmuir pressure, which indicate that temperature and pressure are really important for methane sorption capacity. The extended Langmuir and Dubinin–Radushkevich models have been improved to calculate the methane sorption capacity of shales, which can be described as a function of temperature and pressure. By means of using the two estimation algorithms established in this study, we may draw the conclusion methane sorption capacity can be obtained as a function of depth under geological reservoir. Due to the dominant effect of pressure, methane sorption capacity increases with depth initially, till it reaches a maximum value, and then decrease as a result of the influence of increasing temperature at a greater depth. Approximately, the maximum sorption capacity ranges from 400 m to 800 m.